Towards Students’ Mathematics Self-efficacy and Mathematics Anxiety in Iranian University Context - Ali Mahmoudifar; Maryam Beiki (Journal of Mathematics and Mathematics Education, 2024)
AbstractTeaching is a dynamic process of communication in which students and instructors continually interact together based on the situations and objectives that must be satisfied in the academic context. Anxiety concerning a specific subject is experienced by most students in the academic context, particularly in mathematics. Teaching practices, self-efficacy, and students’ anxiety in class settings directly contribute to the realization of educational objectives. Accordingly, in the university context mathematics attainment is commonly influenced by students’ self-efficacy, and their level of anxiety. The current study tried to scrutinize the relationship between mathematics freshmen students’ self-efficacy and their anxiety level on their academic enactment. This study was conducted on a group of 120 freshmen university students from different faculties who have experienced mathematics course in their classes in Islamic Azad University North Tehran Branch. In the questionnaires, students were asked to express their ideas related to different phases of teaching math in their classes. The questionnaires were adapted based on the Iranian teaching context to evaluate university students’ mathematics self-efficacy and mathematics anxiety. The outcomes of Pearson Correlation (r (118) = -.654 represented a large effect size, p < .05) specified that there was a significant, negative, and large relationship between self-efficacy and anxiety. The outcomes of the current study are also helpful for instructors who wish to gain better insight into their students’ mathematics self-efficacy and anxiety to enhance their students’ attainment.